Examination of feedback tool using interactive movie database for synchronized swimming - Shimizu, J.; Miyaji, C.; Ito, K. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to determine apposite quality conditions (movie format, bit rate, etc...) and apposite methods for visual feedback service via the Internet in synchronised swimming. Therefore we examined the most common movie formats (movie quality encoded at 1Mbps bit rate) and, examined efficacy of searching for movies in a database. We suggest that generally the Windows Media movie format is the most useful movie format. When users (athletes) browse movies via the Internet, they usually can not obtain any advices from their coaches, as a solution for this problem we suggest that users (athletes) should be able to browse annotation at the same time.